2020
DOI: 10.1016/j.chom.2020.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Rapid Transmission of SARS-CoV-2 in Ferrets

Abstract: Graphical Abstract Highlights d SARS-CoV-2-infected ferrets exhibit elevated body temperature and virus replication d SARS-CoV-2 is shed in nasal washes, saliva, urine and feces d SARS-CoV-2 is effectively transmitted to naive ferrets by direct contact d SARS-CoV-2 infection leads acute bronchiolitis in infected ferrets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
1,047
1
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 903 publications
(1,172 citation statements)
references
References 21 publications
58
1,047
1
26
Order By: Relevance
“…SARS-CoV-2 transmission in experimental animal models has recently also been described by others. SARS-CoV-2 direct contact transmission between ferrets 21 and hamsters 22 was reported, with similar efficiency as observed in our study. In addition, SARS-CoV-2 was also found to be transmitted via the air in two out of six ferrets 21 , and in two out of six cats 23 .…”
Section: Figuresupporting
confidence: 91%
“…SARS-CoV-2 transmission in experimental animal models has recently also been described by others. SARS-CoV-2 direct contact transmission between ferrets 21 and hamsters 22 was reported, with similar efficiency as observed in our study. In addition, SARS-CoV-2 was also found to be transmitted via the air in two out of six ferrets 21 , and in two out of six cats 23 .…”
Section: Figuresupporting
confidence: 91%
“…However, the unphysiologically high expression level of ACE2 driven by the ubiquitous K14 promoter may not recapitulate the human disease caused by SARS-CoV-2. Recently, a ferret model of SARS-CoV-2 infection was established that mimics transmission and recapitulates aspects of human disease (Kim et al, 2020). Our study found that ACE2 from multiple species of laboratory animals, including but not limited to ferrets, crab-eating macaques, and Chinese hamsters could be utilized by SARS-CoV-2 to mediate viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is expressed in a diverse range of species throughout the subphylum Vertebrata . Several recent studies demonstrated that ferrets, cats, dogs and some non-human primates are susceptible to SARS-CoV-2 (Kim et al, 2020; Lu et al, 2020; Rockx et al, 2020; Shi et al, 2020; Zhang et al, 2020a). However, the exact host tropism of SARS-CoV-2 remains unknown and is an urgent area to explore for identifying other putative zoonotic reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Since December of 2019, scientists all over the world have been working to establish animal model of COVID-19. So far there are several models reported in preprinted journals or peer-reviewed published journals, including two small murine models (hACE2 transgenic mouse 14 and Gold Syrian hamster 15 ), one ferret model 16 Retrospective studies of clinical features of COVID-19 show that older patients have more severe diseases, which may be associated with comorbidities, including tumor, diabetes, obesity, hypertension, heart diseases and so on [18][19][20] . These underlying diseases may make senior patients more susceptible to SARS-CoV-2 infection and worsen COVID-19.…”
Section: Sars-cov-2 Recently Reported As Another Novel Coronavirus Ementioning
confidence: 99%